2015
DOI: 10.1371/journal.pone.0130259
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a High Fat Diet and Voluntary Wheel Running Exercise on Cidea and Cidec Expression in Liver and Adipose Tissue of Mice

Abstract: Cidea and Cidec play an important role in regulating triglyceride storage in liver and adipose tissue. It is not known if the Cidea and Cidec genes respond to a high fat diet (HFD) or exercise training, two interventions that alter lipid storage. The purpose of the present study was to determine the effect of a HFD and voluntary wheel running (WR) on Cidea and Cidec mRNA and protein expression in adipose tissue and liver of mice. A HFD promoted a significant increase in Cidea and Cidec mRNA levels in adipose t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 45 publications
(60 reference statements)
4
14
0
Order By: Relevance
“…Elevated CIDEA expression and diminished PRKACA , which phosphorylates and activates HSL, suggests that lipolysis was inhibited in tumour-bearing animals. This finding is consistent with previous studies reporting larger lipid droplets, diminished lipolysis and elevated triglyceride storage capacity of adipose tissue concurrent with CIDEA overexpression in adipose tissue [ 23 , 24 ]. It should be noted that depending on the time (stage) of tumour growth and type of adipose tissue, previous studies have reported either smaller or larger adipocytes in tumour-bearing animals [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…Elevated CIDEA expression and diminished PRKACA , which phosphorylates and activates HSL, suggests that lipolysis was inhibited in tumour-bearing animals. This finding is consistent with previous studies reporting larger lipid droplets, diminished lipolysis and elevated triglyceride storage capacity of adipose tissue concurrent with CIDEA overexpression in adipose tissue [ 23 , 24 ]. It should be noted that depending on the time (stage) of tumour growth and type of adipose tissue, previous studies have reported either smaller or larger adipocytes in tumour-bearing animals [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…Cidea and Cidec, localized to lipid droplets and endoplasmic reticulum, are predominantly expressed in adipose tissues and liver, and have been shown to control lipid metabolism in adipocytes and hepatocytes through influencing lipogenesis or lipid droplet formation and to play important roles in the development of metabolic disorders (Gong et al., ; Yonezawa, Kurata, Kimura, & Inoko, ). Reynolds found that a HFD promoted a significant increase in Cidea and Cidec mRNA levels in adipose tissue and liver, and the overexpression of CIDE proteins increased TG accumulation (Reynolds et al., ). Recently, some studies also showed that Cidea and Cidec genes are highly expressed in the fatty livers of aged mice, of type 2 diabetic mice and ob/ob mice (Kelder et al., ; Matsusue et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that exercise training with voluntary wheel reduced body weight and adiposity in diet-induced obese mice as well as normal diet treated lean mice ( Reynolds et al, 2015 ). Consistently, body weight was significantly decreased with the reduction of WAT weights in Exe after 6 weeks of voluntary wheel running in this study ( Fig.…”
Section: Discussionmentioning
confidence: 99%